Evaluation of resistive index of the prostate and bladder sonomorphologic parameters as replacements for urodynamics to predict bladder outlet obstruction in patients with lower urinary tract symptoms suggestive of benign prostatic hyperplasia. Issue 3 (22nd February 2019) - Garg, Gaurav; Sankhwar, Satya Narayan; Goel, Apul; Pandey, Siddharth; Sharma, Deepanshu; Parihar, Anit
Abstract : Objective: This study investigated whether the resistive index (RI) of prostate and bladder sonomorphologic parameters (total prostate volume [TPV], detrusor wall thickness [DWT], intraprostatic protrusion [IPP]) can be used instead of urodynamic studies (UDS) to predict bladder outlet obstruction (BOO) in benign prostatic hyperplasia (BPH) with lower urinary tract symptoms (LUTS). Methods: Men aged ≥50 years with clinical BPH/LUTS were prospectively enrolled included. Basic evaluations, measurement of sonomorphologic parameters, and UDS were performed in accordance with the International Continence Society's Good Urodynamics Practices protocol. Results: Data of 240 patients were divided into two groups based on the BOO index(BOOI). Group 1 consisted of patients negative for BOO (BOOI <40), whereas Group 2 consisted of patients positive for BOO (BOOI > 40). Patient age, International Prostate Symptom Score (IPSS), quality of life score and post‐void residual volume were comparable between the two groups, whereas significant differences were evident in peak flow rate, TPV, DWT, RI, and IPP ( P  < 0.01 for all). Pearson correlation analysis revealed a significant correlation between BOOI and DWT ( r  = 0.198, P  = 0.002), IPP ( r  = 0.450, P  = 0.000), and RI ( r  = 0.334, P  = 0.000). Multiple regression analysis revealed a significant correlation between BOOI and IPP (β = 0.382, P  = 0.000) and RI (β = 0.226, P  = 0.000). Receiver operating characteristic analysis showed that the area under curve was 0.785 for RI (95% confidence interval [CI] 0.703–0.867, P  < 0.001) and 0.905 for IPP (95% CI 0.850–0.961, P  < 0.001). At a cut‐off value of 7.5 mm for IPP, the sensitivity was 86.9%, specificity was 83.3% and positive predictive value was 92.41%. Conclusion: IPP and RI may be the best non‐invasive predictors for BOO in selected patients with LUTS/BPH.